2007
DOI: 10.1016/j.eururo.2007.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Lower Urinary Tract: The Association of Urologic and Sexual Symptoms with Common Illnesses

Abstract: Objective-In addition to being prevalent and bothersome, urologic and sexual symptoms may be related to chronic medical illnesses. We investigate the relationship between ten urologic and sexual symptoms and four major illnesses (type II diabetes, cardiac disease, hypertension, and depression).Methods-We analyze data from the Boston Area Community Health (BACH) Survey, a community-based epidemiologic study of urologic symptoms and risk factors. BACH used a twostage stratified cluster sampling design to recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 53 publications
5
68
0
4
Order By: Relevance
“…In addition to being a validated measurement, this abbreviated form of the FSFI offered a multidimensional assessment of sexual functioning that also permitted comparisons that have been limited in other studies where questions were worded too differently to allow for comparison of results (30,45,47). The FSD prevalence rate in BACH was 34% (48), which compared favorably with previous studies of sexual functioning (35).…”
Section: Measurement Of Female Sexual Functioningsupporting
confidence: 75%
“…In addition to being a validated measurement, this abbreviated form of the FSFI offered a multidimensional assessment of sexual functioning that also permitted comparisons that have been limited in other studies where questions were worded too differently to allow for comparison of results (30,45,47). The FSD prevalence rate in BACH was 34% (48), which compared favorably with previous studies of sexual functioning (35).…”
Section: Measurement Of Female Sexual Functioningsupporting
confidence: 75%
“…29,30 Somatic comorbidity was entered into our multivariate analysis but showed no significant association with low PISQ-12 scores. We recognize that assessing the impact of comorbidity on lower urinary tract and sexual function may require sophisticated tools, developed and validated specifically for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturia is age-related and both genders have a similar prevalence (5)(6)(7). In previous epidemiologic surveys, the prevalence of nocturia ( 2 episodes per night) showed great variation, from 10% (5) to 30% (6,7), depending upon the study population and methodology.…”
Section: Introductionmentioning
confidence: 99%
“…In previous epidemiologic surveys, the prevalence of nocturia ( 2 episodes per night) showed great variation, from 10% (5) to 30% (6,7), depending upon the study population and methodology. Despite the variations, the reports revealed that nocturia is a non--specifi c, but common urinary symptom.…”
Section: Introductionmentioning
confidence: 99%